UK advanced practice nurses’ experiences of the COVID-19 pandemic: a mixed-methods cross-sectional study - Angela Tod; Anthony Ryan; Rachel King; Bethany Taylor; Emily Wood; Michaela Senek; Steve Robertson (BMJ Open)
Objective The aim of the study was to understand the experiences of advanced practice nurses (APNs) in the UK during the 2020 COVID-19 pandemic, particularly in relation to safety, shortages and retention.Design A cross-sectional, mixed-methods survey.Setting APNs in any UK setting.Participants The survey was sent to an existing UK-wide cohort of APNs. 124 APNs responded (51%).Results UK-based APNs in this study reported shortages of staff (51%) and personal protective equipment (PPE) (68%) during the first 3 months of the coronavirus outbreak. Almost half (47%) had considered leaving their job over the same 3 months. Despite difficulties, there were reports of positive changes to working practice that have enhanced care.Conclusion UK APNs report COVID-19-related shortages in staff and equipment across primary and secondary care and all regions of the UK. Shortages of PPE during a pandemic are known to be a factor in the development of mental health sequelae as well as a risk factor for increased turnover and retention issues. Half of APNs surveyed were considering a change in job. The UK risks a further crisis in staff morale and retention if this is not acknowledged and addressed. APNs also expressed concern about patients not receiving routine care as many specialties closed or reduced working during the crisis. However, there were also many examples of good practice, positive changes and innovation.